A Randomized Single‐Blinded Trial of Posttonsillectomy Liposomal Bupivacaine among Adult Patients. (31st July 2018) - Olson, Michael D.; Moore, Eric J.; Price, Daniel L.
Abstract : Objective: To determine whether liposomal bupivacaine (Exparel) is safe and effective in the management of posttonsillectomy pain among adult patients. Study Design: A prospective single‐blind randomized controlled trial. Setting: An academic quaternary care center (Mayo Clinic, Rochester, Minnesota). Subjects and Methods: From May 2015 to December 2016, 39 patients were randomized to receive oral pain medication and 8 mL of injected liposomal bupivacaine or oral pain medication alone for treatment of their posttonsillectomy pain. Visual analog scale pain intensity scores, oral pain medication usage, liquid oral intake, and complications were recorded for 2 weeks after the procedure. Results: Thirty‐nine patients were randomized, with 17 patients in the liposomal bupivacaine group and 22 in the control group. Fifteen patients in the liposomal bupivacaine group and 18 patients in the control group completed the study. Pain intensity score on postoperative day 1 ( P =. 043) proved to be the only statistically significant result, with no difference noted in pain scores on postoperative days 2 to 14. There was no difference in pain medication usage, liquid oral intake, postoperative hemorrhage, or adverse events between groups. Conclusions: The injection of liposomal bupivacaine in the posttonsillectomy wound bed demonstrates improved pain intensity scores for the first 24 hours after surgery with no adverse complications noted in comparison with patients who did not receive the injection. Given the limited pain reduction and increased cost, use of liposomal bupivacaine in adult tonsillectomy patients appears to have minimal indication for use.